Cybersecurity risks and inheritance of digital assets in Kenya: strategies for minimizing losses - Mburu, B. W. (Strathmore University, 2024)
This dissertation investigates the cybersecurity risks associated with the inheritance of digital assets, particularly focusing on cryptocurrency, in Kenya. The emergence of digital assets presents unique challenges for estate planning and inheritance due to their electronic nature and reliance on complex security measures. The study aims to explore the legal and regulatory framework governing digital assets inheritance, identify cybersecurity risks, and propose strategies to minimize these risks. The research employs a qualitative methodology, drawing on secondary sources such as academic articles, legal documents, and reports. Analysis of existing literature and case studies reveals common cybersecurity threats including hacking, phishing attacks, and unauthorized access. The study also examines the current legal landscape in Kenya, highlighting the absence of specific legislation governing digital assets inheritance, and compares it with regulatory frameworks in other jurisdictions. Based on the findings, recommendations are formulated to enhance the legal and regulatory framework for digital assets inheritance in Kenya. Strategies for minimizing cybersecurity risks include comprehensive estate planning, secure storage of private keys, and implementation of multi-factor authentication. The study contributes to the understanding of cybersecurity risks associated with digital assets inheritance and provides valuable insights for policymakers, regulators, and individuals involved in estate planning. It underscores the importance of developing a robust legal framework and adopting proactive cybersecurity measures to safeguard digital assets and ensure their secure transfer across generations.
Full -text undergraduate research project